MAKING OF DISEASE SPREAD IN BOGOR CITY USING GEOGRAPHICAL INFORMATION SYSTEM (GIS) - Dessy Apriyanti; Adi Prayitno (Jurnal Scientia, 2023)
The success of health development in the future will include factors such as ease of access to health and continuous improvement in the quality of health services. The city of Bogor is located between 106' 48' east longitude and 6' 26' south latitude, Administratively, the city of Bogor consists of 6 districts. With a fairly densely populated city, of course, the level of health is quite low, where Bogor is a city with high rainfall. where there are many types of diseases that appear in the rainy season, for example: Acute Nashoparyngitis, Essential Primary, Acute Respiratory Tract, and others. Therefore, it is necessary to make a map of the distribution of diseases in Bogor City using the Geographic Information System method. The use of a geographic information system (GIS) involves presenting data and information in the form of a map which can be used as an attractive and varied presentation tool according to needs. The main function in using GIS in this modern era is that maps are no longer the end result in an activity because GIS can facilitate the output of the resulting maps. The results obtained in this study are the distribution of the top five types of diseases in Bogor City from January to June 2020, namely Acute nasopharyngitis [common cold], Essential (primary) hypertension, Upper respiratory tract infections, Dyspepsia, and Myalgia, The total number of infected The top 5 diseases are as many as 210,626 people from 6 sub-districts in Bogor City.